AMBIGUITAS MULTIKULTURALISME DALAM NOVEL MATA-MATA KUCING: SEBUAH FABEL MULTIKULTURAL DAN MARYAM - Resti Nurfaidah (Faculty of Humanities, Jember University, 2012)
This article discusses the ambiguity that occurs in the perspective of multiculturalism. Ongoing crosscultural dialogue between cultures with each other, influence each action antarunsur role of culture caused by the outflow of people or groups of people from one place to another place in the diaspora effect, is a form of multikulturaisme. Multiculturalism can not be fully accepted in this country, as reflected in the novel’s two MataMata Kucing: Sebuah Fabel Multikultural and Maryam. Most of the proponents of multiculturalism may be able to easily access the diversity of it, but for the others who do not understand or have knowledge of such multiculturalism, it will lead to conflict as reflected from the two novels that became the object of study. The result can be unpredictable if prolonged disputes and even stretch interval proximity relationships between individuals. Keywords: ambiguity, diaspora, multiculturalism.